Analisis Video Pertandingan Tim Putra Floorball Jawa Timur pada Final Eksibisi PON XXI Aceh-Sumut 2024 - M Irfan Bagus Saputro; Fatkur Rohman Kafrawi; Heri Wahyudi; Roy Januardi Irawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research was conducted to look at team components starting from the strengths and weaknesses of the team so that it can be used as evaluation material to make better improvements to the team to face the next match. This research also aims to confirm the findings of video analysis in the final match of the East Java Floorball men's team at the 2024 Aceh-Sumut PON XXI exhibition. This research methodology uses quantitative descriptive, which uses match video analysis data to paint a picture or reveal information about the facts. facts about the final field for the men's floorball team in East Java. The sample from this research was the East Java Floorball men's team who were the core players or who only played in the final round. The researcher's data sheet on video match analysis served as a tool. The quantitative descriptive data analysis method was applied using figures obtained from video study findings and evaluation results. From the results of video analysis of the final match of the East Java Floorball men's team, when compared with other strategies, it was found that the tactics of passing and controlling the ball gave the best results. Players gain an advantage when the opposing team has the ball as a result of frequently using this method and developing their game. The East Java Floorball men's team has better ball control than its opponents because their passing technique and ball control are superior.